STRATEGI MARKETING MIX, YIELD MANAGEMENT, CUSTOMER SATISFACTION AND OCCUPANCY RATE - Ramia Adnyana; Gede Sri Darma (Universitas Pendidikan Nasional, 2015)
of this research is to understand and analyses the relationship betweenmarketing mix, yield management strategy, customer satisfaction and occupancy rate diFurama Villas & Spa, Badung, Bali.Occupancy rate influence by four factor such as the correct implementation ofmarketing mix strategy, yield management strategy and how to manage the customersatisfaction in order to increase the sales performance especially determine through occupancyrate. The four factor are clearly shown on the response from the customer through the answerfrom the distributed questionnaire using the Score Interval Scale.This research study includes the four hypothesis that would be examined. Data from100 respondents selected by using non-probability technique with purposive or judgmentsampling method was analyzed with Structural Equation Model (SEM) analysis by usingAMOS version 20.0 software. The result of this research proved that the relationship amongthe four variable strategi marketing mix strategy, yield management, customer satisfactionshow the positive and strong influence to increase the occupancy rate. The result is betweenthe rane of Goodness of Outfit criteria : Chi-square =209,594 : probability = 0,03 ; RMSEA= 0,023 ; GFI = 0,917 ; AGFI = 0,914; CMIN / DF = 0,872 ; TLI = 0,802 ; CFI = 0,894; Allof the hypothesis in this research can be accepted.This research also connect results of the research with theoretical implicatiob andpolicy implication for the management of Furama Villas & Spa, Badung Bali as elaborated inthe summary and epilog. Limitation of the research agenda and future research can be adjustedto all the upcoming research.Keywords: strategy, marketing mix, yield management, customer satisfaction and occupancyrate.